Medical Imaging 2013: Image Perception, Observer Performance, and Technology Assessment 2013
DOI: 10.1117/12.2006987
|View full text |Cite
|
Sign up to set email alerts
|

A study of the feasibility of using slabbing to reduce tomosynthesis review time

Abstract: This study aimed to investigate whether decreasing the amount of slices in breast tomosynthesis (BT) image volumes reduce reading time. BT slices were combined into so-called slabs, by reconstructing thin slices and merging them into thicker slabs. Sets of slabs where created from 35 clinical BT volumes with malignant or benignant findings and from 50 BT volumes drawn from screening sets (without any prior review). The image sets were reviewed in two separate sessions while the review time was recorded. A tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…We did not register the reading time in our study, since the reading and scoring procedures were specific to the trial and would not reflect the true time consumption in a normal screening workflow. In a previous study from our group, we found that the reading time for one-view DBT (MLO) was roughly 30 s (in an enriched population of clinical and screening cases) [ 27 ]. This is about one third of the reported reading time for the so-called combination mode — two-view DBT in combination with two-view DM — used in the Oslo Tomosynthesis Screening Trial [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…We did not register the reading time in our study, since the reading and scoring procedures were specific to the trial and would not reflect the true time consumption in a normal screening workflow. In a previous study from our group, we found that the reading time for one-view DBT (MLO) was roughly 30 s (in an enriched population of clinical and screening cases) [ 27 ]. This is about one third of the reported reading time for the so-called combination mode — two-view DBT in combination with two-view DM — used in the Oslo Tomosynthesis Screening Trial [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“… 7 To the best of our knowledge, no study of reading time for one-view DBT compared with two-view DM is available. However, two studies reported reading times of one sided one-view wide-angle DBT 8 , 9 . These times were similar to the DBT reading times in some of the studies comparing one-sided two-view DBT with DM, 6 , 7 but shorter than some of the studies 4 , 5 .…”
Section: Introductionmentioning
confidence: 61%
“…That depends on if radiologists spend an equal amount of time on all slice images, or routinely go through the outer parts of the image volume faster. However, earlier studies suggest that increased slab thickness reduces the reading time [7] . Furthermore, during the image evaluation in this work, there was a wait for the standard image volumes (2 mm slab thickness) to upload to the workstation, while the smaller image volumes (6 mm and 10 mm slab thickness) was uploaded almost instantaneous.…”
Section: Discussionmentioning
confidence: 99%
“…This can be done by combining adjacent image planes into thicker slice images, so called slabbing [7,8] . Since thicker slabbing decreases the depth resolution, and thereby increases tissue overlap, it could affect the detection of lesions [9,10] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation